When breaks the dawn - Oke, Janette, 1935- (Canadian West ;, 1986)
After surviving a harsh first year in the far north, Elizabeth Delaney and her Royal Canadian Mountie husband, Wynn, are settling into the small community of Beaver Creek. Elizabeth is once more teaching school, and they seem to be gradually making a place for themselves among the Indians. And then the news arrives...